Ultrasound-Assisted Emulsification Microextraction Based on Solidification Floating Organic Drop Trace Amounts of Manganese Prior to Graphite Furnace Atomic Absorption Spectrometry Determination - Alireza Mohadesi; Masoumeh Falahnejad (The Scientific World Journal)
In the present study, an ultrasound-assisted emulsification microextraction based on solidification floating organic drop method is described for preconcentration of trace amounts of Mn (II). 2-(5-Bromo-2-pyridylazo)-5 diethylaminophenol was added to a solution of Mn+2 at ph = 10.0. After this, 1-undecanol was added to the solution as an extraction solvent, and solution was stirred. Several factors influencing the microextraction efficiency, such as pH, the amount of chelating agent, nature and volume of extraction solvent, the volume of sample solution, stirring rate, and extraction time were investigated and optimized. Then sample vial was cooled by inserting into an ice bath, and the solidified was transferred into a suitable vial for immediate melting. Finally the sample was injected into a graphite furnace atomic absorption spectrometry. Under the optimum condition the linear dynamic range was 0.50–10.0 ng mL−1 with a correlation coefficient of 0.9926, and the detection limit of 0.3 ng mL−1 was obtained. The enrichment factor was 160. The proposed method was successfully applied for separation and determination of manganese in sea, rain, tap, and river water samples.